Data-driven Model Development for Quality Prediction in Forming Technology - Kirchen, Iris; Vogel-Heuser, Birgit; Hildenbrand, Philipp; Schulte, Robert Karl; Vogel, Manfred; Lechner, Michael; Merklein, Marion (15th IEEE International Conference on Industrial Informatics (INDIN), 2017)
this investigation data recorded from a flexible rolling process is processed by data driven methods to develop a quality prediction model for manufactured blanks. A concept for an incremental prediction method is proposed, which takes into account the specific character of the discrete manufacturing process. The method is evaluated based on a data set of process and quality data provided by a test rig. By the example of a specific quality parameter the effectiveness of the proposed method is confirmed. A precise quality prediction model is developed, which predicts the quality value with a high accuracy.
LFT Import::2019-08-05 (2252)
Keywords: automated Production Systems; data analytics; quality prediction